The Effect of Firm Size and Public Accounting Firm Size on Audit Quality with Audit Fee as a Moderating Variable (Survey on Property and Real Estate Companies Listed on IDX in 2022–2024) - Ahmat Bayu Sepriyanto; Sri Rahayu; Salman Jumaili (Cita konsultindo, 2025)
This study examines how company size and the size of the Public Accounting Firm (KAP) affect audit quality; the moderating variable is audit fees. The high complexity of reporting in the property and real estate industry, along with issues related to financial statement manipulation and delays, underpins this research. This study employs a quantitative method using Moderated Regression Analysis (MRA) on property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The results show that audit firm size does not affect audit quality, but firm size does. Furthermore, there is no evidence that audit fees moderate the relationship between audit quality and firm or firm size. This study is expected to improve the quality of business governance and the effectiveness of external audits in the property and real estate industry.